Evaluasi Supplier Bahan Baku Plat Besi Dengan Menggunakan Metode Analytical Hierarchy Process Dan Taguchi Loss Function - Wildatul Khoiro (Department Industrial Engineering, University of Muhammadiyah Malang, 2015)
PT. Lamongan Marine Industry is a manufacturing company that produce large ships. The company have contracts with four suppliers of iron plate. In cooperation with these suppliers, they unable to meet the quality standards for iron plate is a measure of the thickness of the thick 45 mm. Material defects from suppliers thickness is less the limit set by the company is 0,3 mm – 0,5 mm. Process evaluation of the suppliers performed to look for suppliers that meet the criteria of the company. In this study, supplier evaluation process is carried out using Analytical Hierarchy Process (AHP) and Taguchi Loss Function (TLF). AHP for wighting each of criterian, while TLF for calculating loss function each of supplier. Criterian of the supplier evaluation are price, quality, delivery, underweight, availability, payment system, guarantee policy and repair service, with wight for each criterion are 6%, 6%, 8%, 15%, 17%, 13%, 8% and 26%. The results showed that the best supplier that meets the company criteria is a supplier PT. Biz Fitting with loss Rp. 1.140.973.